Dried distillers grains supplemented at different frequencies to stocker heifers grazing late-season Flint Hills native pastures - M.P. Epp; W.L. Metzen; Brandon E. Oleen; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2010)
Wetter-than-normal summer grazing seasons can produce excessive forage beyond what the typical Flint Hills double-stock harvest rate can remove. These late-summer native grasses do not contain adequate protein to sustain economical gains for stocker cattle, but producers can extend the grazing season by using a protein-based supplement to generate economically feasible rates of gain. Use of dried distillers grains as a supplementation program can help promote overall productivity during the fall grazing season. However, the drawback is the potential high labor input for supplement delivery. Delivering supplements at reduced frequencies per week may be able to sustain daily gains of stocker cattle while reducing labor costs associated with supplement delivery.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Dried distillers grains; Stocker heifers; Protein; Daily gain